Managing Goals in the Implementation of Corporate Social and Environmental Responsibility Programs in North Kalimantan Province - Tanduklangi, Ferdi Manurun; Ibrahim, Muh. Akmal; Haning , Moh. Thahir; Ahmad , Badu (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
This study is intended to determine how the implementation of Managing Goals in the Implementation of Corporate Social and Environmental Responsibility Programs in North Kalimantan Province. By that contained in the Regulation of the Governor of North Kalimantan Province Number 11 of 2023. The data is then compiled in a qualitative study. Based on the results of the study, the research findings show that there are differences in the objectives of the three main elements of this TJSLP program. Starting from companies that see this program not purely as a development program but also as a fulfillment of obligations and the government and society view this program as a whole as sustainable development of the social environment of the North Kalimantan community. As well as the differences in the roles carried out by each stakeholder element in implementing the TJSLP program in North Kalimantan Province.